Contemplating or Acting? Which Immersive Modes Should Be Favored in Virtual Reality During Physiotherapy for Breast Cancer Rehabilitation - Buche, Hélène; Michel, Aude; Piccoli, Christina; Blanc, Nathalie (Frontiers in Psychology, 2021)
Background: Even though virtual reality is more and more considered for its power of distraction in different medical contexts, the optimal conditions for its use still have to be determined in order to design interfaces adapted to therapeutic support in oncology. Objective: The objective of this study was to examine the benefits of VR using two immersion methods and comparing them with each other in a population of women with breast cancer who have undergone breast surgery. Methods: During the physiotherapy rehabilitation course, each patient participated in four sessions in random order: two under virtual immersion (i.e., one participatory, one contemplative), one under musical listening and one without special assistance other than the one given by the practitioner. The impact of the level of patient involvement in the virtual world was apprehended through the evaluation of the feeling of presence; the estimation of elapsed time of the physiotherapy sessions and particular attention was paid to the evaluation of patient emotional state. Results: Our study showed an increase in positive emotions (i.e., joy and happiness) and a decrease in anxiety regardless which support methods were offered. Participatory VR created a feeling of more intense spatial presence. Conclusion: Our results highlight the importance of the context in which virtual reality should be offered. The presence of the practitioner and his interactions with the patient can provide a context just as favorable in reducing anxiety as the emotional regulation tools used (VR, music). The use of technological tools should be favored when the practitioner is unavailable during the treatment phase or, even, in order to reduce the monotonous nature of repetitive therapeutic sessions.